The complete mitochondrial genome of the endangered Chinese black-necked pond turtle, Mauremys nigricans - Zhao, Jian (Mitochondrial DNA B Resour, 2016)
The complete mitochondrial genome of the endangered Chinese black-necked pond turtle, Mauremys nigricans, was determined in this study. The mitogenome was 16 779 bp in length, and the GC content was 39.07%. The genomes encoded 37 genes typically found in other vertebrates. In the control region, three CSBs were identified, followed by long tandem repeats of (ATATCATATT)(10)(ATATC)(ATATATC)(7)(TA)(102). The mitochondiral genome sequence would be useful for the phylogenetic and conservation studies of Asian endangered turtles.